The Role of FT. Intelkam in Monitoring Demonstrations in the Mojokerto Police Area (Advances in Police Science Research Journal, 2024)
Mojokerto Regency is an industrial center with labor demonstrations a common occurrence. This demonstration was triggered by various demands such as industrial relations issues and unilateral termination of employment relations. The police have a role in maintaining public order and security, including handling demonstrations. This research aims to understand the dynamics of labor demonstrations in Mojokerto in 2023, the role and function of Intelkam in organizing demonstrations, as well as efforts to optimize Intelkam in this regard. The research method used is qualitative with case studies. The research subjects included the Mojokerto Police Intelligence and Security Unit, representatives of protesting workers, and other related parties. Data was obtained through interviews, document study, observation, and FGD. The research results show that labor demonstrations are predominantly influenced by industrial relations issues such as wage demands and job layoffs. Intelkam plays a role in collecting and analyzing information related to demonstrations and then transferring this to officers in the field. Apart from that, the Mojokerto Police have also provided training to improve the quality of Intelkam human resources and optimize their role.
Keywords: intelkam; unjuk rasa buruh; optimalisasi